Landscape-climatic features of the reforestation dynamics pyrogenically transformed geosystems of the Tunkinskaya depression. Issue 1 (October 2021) - Atutova, Zh V; Voropay, N N; Shuklina, E S
Abstract: In order to identify the features of the dynamics of the soil temperature regime during the post-fire restoration of the subtaiga light-coniferous geosystems of the Tunkinskaya depression, a study of the demutation processes in the pine forests of the Badar urochishche was conducted. Our research is based on the data of observations initiated after the fire that took place in 2010. The model key areas were selected at intact landscape complexes that did not experience pyrogenic influence, as well as the territory subjected to forest fires. Comparing the dominant composition of secondary succession biocenoses with natural plant communities in the background key area, indicators of the prospects for successful reforestation were identified. The analysis of 10-year data on the observation of the soil temperature regime from the surface to a depth of 3.2 m was carried out at the selected sites. The differences between the soil temperatures in the disturbed and natural sites, which vary during a year were revealed. During the observation period, a decrease in microclimatic differences was observed with the regeneration of vegetation cover, which indicates the restoration of the temperature regime in the pyrogenic-disturbed area.